2021
DOI: 10.1080/21655979.2021.1962684
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane promotes the apoptosis of laryngeal squamous cell carcinoma in-vitro and inhibits its malignant progression via miR-26a/FOXO1 axis

Abstract: Laryngeal squamous cell carcinoma (LSCC) is a laryngeal malignancy with a high mortality rates, and its treatment remains difficult. Sevoflurane is a surgical anesthesia which has anti-tumor effect. This investigation assessed the effects of LSCC cells treatment with Sevoflurane in vitro and in vivo. Hep-2 and Tu177 cells, human LSCC samples and BALB/C nude mice were used for result assessments. Cell viability, proliferation, migration and invasion were assessed via Cell Count Kit-8, wound healing assay and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Sevoflurane is an inhalational anesthetic with common application in surgery. Studies have shown that sevoflurane affects cancer progression and inflammations via mediating signaling pathways and gene expressions [ 7 , 8 ]. It altered pathophysiological situations of brain, which leads to neuroinflammation and results in neurodegenerative changes.…”
Section: Introductionmentioning
confidence: 99%
“…Sevoflurane is an inhalational anesthetic with common application in surgery. Studies have shown that sevoflurane affects cancer progression and inflammations via mediating signaling pathways and gene expressions [ 7 , 8 ]. It altered pathophysiological situations of brain, which leads to neuroinflammation and results in neurodegenerative changes.…”
Section: Introductionmentioning
confidence: 99%
“…Of those, 166 were excluded for describing HNSCC cases without focus on the larynx ( n = 28), for being exclusively in vitro studies ( n = 39), for having a number of patients less than 10 or for using patient data from public databases ( n = 50), for not quantifying miRNAs in patient samples ( n = 43) and for other reasons, such as for not having statistically significant results or wrong miRNA sequence ( n = 6). Finally, the review was performed on a total of 177 studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 …”
Section: Resultsmentioning
confidence: 99%
“…One miRNA, miR-26a-5p, was described with opposite roles in two studies [ 53 , 108 ]. For this reason, this miRNA was not included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…46 Also, sevoflurane promotes the apoptosis of laryngeal squamous cell carcinoma in-vitro and inhibits its malignant progression via miR-26a/FOXO1 axis. 47 In a large number of glioma studies, sevoflurane has shown anti-tumor effects through multiple miRNA pathways, For example, increasing the expression of miR-637, 48 miR-124-3p, 49 miR-34a-5p, 50 miR-146b-5p, 28 miR-210, 51 miR-27b, 52 or miR-144-3p 53 to regulate its corresponding downstream molecules and inhibit the migration and invasion of glioma cells. In addition to directly acting on miRNA, sevoflurane can play a regulatory role by acting on upstream circRNA.…”
Section: Inhalation Anesthesia and Gene Expressionmentioning
confidence: 99%